A solid oxide fuel cell cathode with a chromium poisoning resistant core-shell structure and a method of making the same

CN123033986APending Publication Date: 2026-11-03ANHUI CHERY GREEN ENERGY ECOLOGICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611200170.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

During long-term operation, commercial SOFC cathodes suffer from performance degradation due to the migration of volatile Cr species from the metal interconnects, which generate high-resistivity chromates that clog the reaction interface. Existing modification solutions have limited effectiveness or high process costs, making it difficult to achieve industrial-scale mass production.

Method used

A core-shell cathode is constructed using a screen-printed LSCF as the core layer and a metal-doped cerium-based oxide as the shell. The shell has a porous structure with a thickness of 10-25 nm and a pore size of 5-12 nm. It is loaded onto the surface of the SOFC half-cell with a GDC barrier layer and is prepared by vacuum impregnation and stepwise sintering processes to achieve a physical barrier effect, blocking the contact between gaseous Cr and the active sites of the LSCF.

Benefits of technology

It effectively blocks the contact between gaseous Cr and the active sites of LSCF, and no chromate is generated on the cathode surface after long-term operation. It improves the structural stability and catalytic activity of the cathode, reduces polarization resistance, is compatible with a variety of electrolyte systems, and is suitable for industrial-scale batch preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033986A_ABST
    Figure CN123033986A_ABST
Patent Text Reader

Abstract

The application discloses a kind of anti-chromium-poisoning core-shell structure solid oxide fuel cell cathode and its preparation method, the anti-chromium-poisoning core-shell structure solid oxide fuel cell cathode is formed with screen printing LSCF as core layer, with metal-doped cerium-based oxide as shell layer;The shell layer is uniformly coated on the surface of core layer;The cathode is loaded on the surface of SOFC half cell with GDC barrier layer, the cathode has the shell layer of physical barrier effect, can block gaseous Cr and LSCF active site contact, no chromate is generated on the surface of cathode after long-term operation, effectively solve the problem of cathode poisoning attenuation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid oxide fuel cell technology, specifically relating to a solid oxide fuel cell cathode with a core-shell structure resistant to chromium poisoning and its preparation method. Background Technology

[0002] Solid oxide fuel cells (SOFCs) are highly efficient and clean all-solid-state energy conversion devices with broad application prospects. The cathode is responsible for the oxygen reduction reaction, and its performance directly affects the cell's power and lifespan.

[0003] Commercial mainstream LSCF cobalt-based perovskite cathodes exhibit excellent catalytic performance; however, during operation, volatile Cr species precipitate from the metal linker, migrate to the cathode to form highly resistive chromates, block the reaction interface, and cause cathode performance degradation, limiting the large-scale promotion of SOFCs. Existing modification schemes are insufficiently effective, prone to deteriorating initial performance, or have high process costs.

[0004] There is an urgent need to develop cathode modification technologies that combine high catalytic activity, strong resistance to chromium poisoning, and ease of industrial preparation to ensure the long-term stable operation of SOFCs. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a solid oxide fuel cell cathode with a core-shell structure resistant to chromium poisoning and its preparation method. The cathode has a shell layer that acts as a physical barrier, which can block gaseous Cr from contacting the active sites of the LSCF. After long-term operation, no chromate is generated on the cathode surface, effectively solving the problem of cathode poisoning and degradation.

[0006] The present invention also provides a solid oxide fuel cell, which is prepared using the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure described in the present invention as the cathode.

[0007] The technical solution adopted in this invention is as follows:

[0008] This invention provides a solid oxide fuel cell cathode with a chromium-poisoning core-shell structure. The chromium-poisoning core-shell solid oxide fuel cell cathode has a screen-printed LSCF as the core layer and a metal-doped cerium-based oxide as the shell layer. The shell layer uniformly covers the surface of the core layer. The cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer.

[0009] In the metal-doped cerium-based oxide, the molar ratio of cerium to the doped metal element is (8-9.5):(0.5-2).

[0010] The shell layer has a thickness of 10-25 nm and a porous structure with a pore size of 5-12 nm; the LSCF core layer has a printing thickness of 15-25 μm.

[0011] In the metal-doped cerium-based oxide, the doping metal element is any one of gadolinium, samarium, and yttrium.

[0012] The electrolyte material of the SOFC half-cell is any one of YSZ, GDC, and LSGM.

[0013] The present invention also provides a method for preparing the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure, the method comprising the following steps:

[0014] (1) The LSCF cathode paste is uniformly printed on the surface of the GDC barrier layer of the SOFC half cell. After printing, it is pre-baked to obtain the LSCF cathode blank.

[0015] (2) Dissolve the cerium source and the doped metal nitrate in a solvent, stir until homogeneous, and obtain a precursor solution;

[0016] (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to negative pressure for heat preservation; then add the precursor solution to the surface of the cathode blank at a uniform rate, impregnate at normal pressure, and then dry to obtain the impregnated blank;

[0017] (4) Heat the impregnated blank to 300-450℃ and hold for 1-3 hours, then heat to 800-1000℃ and hold for 2-5 hours, and finally cool to room temperature with the furnace to obtain LSCF@metal-doped cerium-based oxide core-shell structure cathode.

[0018] In step (1), the thickness of the printing is 15-25 μm.

[0019] In step (1), the pre-baking conditions are 75-85℃ for 20-30 minutes.

[0020] In step (2), the cerium source is one of cerium nitrate hexahydrate or cerium acetate tetrahydrate.

[0021] In step (2), the doped metal nitrate is any one of gadolinium nitrate hexahydrate, samarium nitrate hexahydrate, and yttrium nitrate hexahydrate.

[0022] In step (2), the solvent is selected from a mixture of deionized water and one of ethanol, ethylene glycol and isopropanol in a volume ratio of 1:1.

[0023] In step (2), the concentration of solute in the precursor solution is 0.15-0.4 mol / L.

[0024] In step (3), the negative pressure is 0.05-0.09 MPa and the heat preservation time is 25-30 min.

[0025] In step (3), the atmospheric pressure immersion time is 15-40 min.

[0026] In step (3), the dropping speed is controlled at 0.5-1 mL / min; the drying conditions are: drying at 60-80℃ for 30-60 min.

[0027] In step (4), the impregnated blank is placed in a muffle furnace. First, the temperature is raised to 300-450℃ at a heating rate of 2-4℃ / min and held for 1-3 hours. Then, the temperature is raised to 800-1000℃ at a heating rate of 3-5℃ / min and held for 2-5 hours. Finally, the blank is cooled to room temperature with the furnace.

[0028] The present invention also provides a solid oxide fuel cell, which is prepared using the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure described in the present invention as the cathode. It has low polarization resistance and small attenuation after long-term operation at high temperature.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. Excellent resistance to chromium poisoning: The solid oxide fuel cell cathode provided by this invention uses metal-doped cerium-based oxide as the shell, which has a physical barrier effect and can block the contact between gaseous Cr and the active sites of LSCF. After long-term operation, no chromate is generated on the cathode surface, effectively solving the problem of cathode poisoning and degradation.

[0031] 2. Extremely strong structural stability: The thermal expansion coefficients of the metal-doped cerium-based oxide shell and the LSCF core are highly matched. During preparation, the internal stress of the metal-doped cerium-based oxide shell is eliminated through a stepwise sintering process. There is no shell shedding, cracking, or agglomeration during long-term high-temperature operation and thermal cycling, and the interface is firmly bonded.

[0032] 3. Simple and controllable process: The method for preparing the solid oxide fuel cell cathode with anti-chromium poisoning core-shell structure provided by the present invention adopts a conventional impregnation-sintering process, which does not require complex equipment and precision operation. The process parameters are adjustable, the repeatability is good, the raw material cost is low, and it is suitable for the industrial mass production of SOFC single cells and battery stacks.

[0033] 4. Wide range of applications: It can be adapted to various medium and low temperature SOFC systems, and is suitable for perovskite cathodes such as LSCF and LSC. It is compatible with existing SOFC production processes and is easy to industrialize. Attached Figure Description

[0034] Figure 1 A process flow diagram for fabricating the chromium poisoning-resistant core-shell structured solid oxide fuel cell cathode provided by this invention;

[0035] Figure 2Polarization impedance of SOFC full cells prepared with solid oxide fuel cell cathodes prepared in each embodiment and comparative example at different initial temperatures.

[0036] Figure 3 SOFC full cells fabricated using solid oxide fuel cell cathodes prepared according to the various embodiments and comparative examples were tested at a temperature of 700°C and a current density of 0.3 A / cm². 2 The polarization impedance was measured after the power generation operation time was different, with H2 flow rate of 500 sccm and air flow rate of 1500 sccm. Detailed Implementation

[0037] Solid oxide fuel cells (SOFCs), as a highly efficient and clean all-solid-state energy conversion device, have advantages such as wide fuel adaptability, high power generation efficiency, no dependence on precious metals, and the ability to provide combined heat and power. They have broad application prospects in distributed power generation, transportation, and energy storage power stations. The cathode, as the core electrode component of an SOFC, undertakes the catalytic task of the oxygen reduction reaction (ORR). Its catalytic activity, conductivity, and structural stability directly determine the battery's output power and service life.

[0038] Currently, commercial SOFC cathodes mostly use cobalt-based perovskite materials, with lanthanum strontium cobalt ferrite (LSCF) being the most widely used. This type of material possesses excellent oxygen reduction catalytic activity and ion-electron mixed conductivity, making it suitable for the operating requirements of medium- and low-temperature SOFCs. However, during actual long-term operation of SOFCs, the iron-chromium alloy metal connector continuously volatilizes gaseous Cr species, such as CrO3 and Cr(OH)2O, under high-temperature oxidizing atmospheres. These volatile Cr substances migrate with the gas flow to the cathode surface, reacting chemically with the active sites of the LSCF cathode to generate high-resistivity, non-catalytically active chromates, such as SrCrO4 and LaCrO3, as byproducts. These chromate byproducts cover the three-phase reaction interface of the cathode, blocking oxygen diffusion channels and ion transport pathways, leading to a sharp increase in cathode polarization resistance and rapid decay of catalytic activity. Ultimately, this results in a significant decrease in battery output power and a substantial reduction in service life, becoming a core technical bottleneck restricting the commercial-scale application of SOFCs.

[0039] Existing modification methods for SOFC cathodes to resist chromium poisoning have the following drawbacks: First, while simply modifying the cathode substrate with elemental doping can inhibit chromate formation to some extent, the modification effect is limited and cannot fundamentally block the contact between Cr species and active sites. Second, using physical coating of protective layers can easily lead to problems such as poor coating density, weak adhesion to the substrate, and high-temperature sintering cracking, which can hinder oxygen ion and electron transport and reduce the initial electrochemical performance of the cathode. Third, the preparation process of some complex cathode structures is cumbersome and costly, making it difficult to achieve industrial-scale mass production.

[0040] To address the above problems, this invention provides a cathode modification technology that combines high catalytic activity, excellent resistance to chromium poisoning, and feasibility of preparation. The specific solution is as follows:

[0041] This invention provides a solid oxide fuel cell cathode with a chromium-poisoning-resistant core-shell structure. The cathode uses screen-printed LSCF as the core layer and a metal-doped cerium-based oxide as the shell layer. The shell layer uniformly coats the surface of the core layer. The LSCF material possesses excellent oxygen reduction catalytic activity and electronic conductivity, serving as the core to ensure the cathode's conductive and catalytic functions. The metal-doped cerium-based oxide possesses good oxygen ion conductivity, high-temperature stability, and anti-sintering properties. As the shell layer, it effectively modifies the surface of the LSCF particles, acting as a physical barrier to block the contact between gaseous Cr and the active sites of LSCF. After long-term operation, no chromate is generated on the cathode surface, effectively solving the problem of cathode poisoning and degradation. Simultaneously, it addresses the shortcomings of LSCF material, such as easy agglomeration at high temperatures, high interfacial impedance, and long-term performance degradation, synergistically achieving two-phase conduction of electrons and oxygen ions, significantly improving the cathode's oxygen reduction reaction efficiency.

[0042] The cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer. The GDC barrier layer can effectively block the interdiffusion of interfacial elements between the LSCF cathode and electrolytes such as YSZ and LSGM, avoid the generation of a high-resistance inert interfacial layer under high-temperature operation, reduce the contact impedance of the battery interface, and improve the bonding stability between the cathode and the half-cell substrate, making it suitable for industrial applications of various electrolyte systems.

[0043] In alternative solutions, the GDC barrier layer can also be replaced with an SDC barrier layer or a YDC barrier layer; the thickness of the barrier layer is preferably 0.5~2 μm.

[0044] In the metal-doped cerium-based oxide, the molar ratio of cerium to the doping metal is (8-9.5):(0.5-2). This ratio enables precise doping modification of the cerium oxide lattice by the doping metal ions, appropriately introducing lattice oxygen vacancies and significantly improving the oxygen ion conduction rate of the cerium-based oxide. If the doping amount is too low, the number of oxygen vacancies will be insufficient, resulting in a weak modification effect. If the doping amount is too high, it will easily cause lattice distortion and grain agglomeration, which will reduce the structural stability and conductivity. This ratio range can achieve the optimal balance between activity and stability.

[0045] The shell thickness is 10-25 nm, and the shell has a porous structure with a pore size of 5-12 nm. The 10-25 nm ultrathin shell can completely encapsulate the LSCF particles, achieving interface modification, without blocking the cathode pores or hindering gas transport, thus avoiding the problems of increased conductivity and polarization caused by an excessively thick shell. The 5-12 nm porous structure matches the pore size requirements for oxygen diffusion, adsorption, and activation, significantly increasing the three-phase interface area of ​​the oxygen reduction reaction, while ensuring smooth gas permeation, taking into account both structural stability and electrochemical activity.

[0046] The printing thickness of the LSCF core layer is 15-25μm, which is the optimal functional thickness range for SOFC cathodes. If the thickness is too thin, there will be insufficient catalytic active material and weak current carrying capacity. If the thickness is too thick, it will easily lead to high gas transmission resistance, increased bulk impedance, and severe polarization.

[0047] In the metal-doped cerium-based oxide, the doping metal element is any one of gadolinium, samarium, and yttrium; the radii of the three rare earth metal ions are well matched with those of cerium ions, and they can be stably doped into the cerium oxide lattice without causing lattice collapse; after doping, a large number of reversible oxygen vacancies can be continuously generated, which improves the medium-temperature conductivity of the material, while effectively inhibiting the high-temperature grain growth of cerium-based oxides, and improving the high-temperature operation stability and anti-aging ability of the cathode.

[0048] The electrolyte material of the SOFC half-cell is any one of YSZ, GDC, and LSGM.

[0049] The present invention also provides a method for preparing the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure, the method comprising the following steps:

[0050] (1) The LSCF cathode paste is uniformly printed on the surface of the GDC barrier layer of the SOFC half cell. After printing, it is pre-baked to obtain the LSCF cathode blank.

[0051] (2) Dissolve the cerium source and the doped metal nitrate in a solvent, stir until homogeneous, and obtain a precursor solution;

[0052] (3) Place the LSCF cathode blank in a vacuum impregnation kettle, close the kettle and evacuate to negative pressure for heat preservation; then impregnate at normal pressure to provide sufficient time for precursor ion adsorption and diffusion, so as to achieve uniform adsorption on the particle surface; then dry to obtain the impregnated blank.

[0053] (4) Heat the impregnated blank to 300-450℃ and hold for 1-3 hours, then heat to 800-1000℃ and hold for 2-5 hours, and finally cool to room temperature with the furnace to obtain LSCF@metal-doped cerium-based oxide core-shell structure cathode.

[0054] In step (1), the pre-drying conditions are 75-85℃ for 20-30 minutes; through low-temperature pre-drying, the solvent in the slurry is removed, forming a flat, dense LSCF cathode blank that is tightly bonded to the barrier layer, laying the foundation for subsequent core-shell structure coating.

[0055] In step (1), the electrolyte of the SOFC half-cell is made of YSZ, GDC or LSGM material.

[0056] In step (1), the printing thickness is 15-25μm and the printing area size is 9cm×9cm.

[0057] In step (1), the printing is preferably screen printing. The screen printing process can precisely control the electrode thickness and size, ensure the uniformity and flatness of the coating, and is suitable for the mass production of large-size half-cells.

[0058] In step (2), the cerium source is either cerium nitrate hexahydrate or cerium acetate tetrahydrate; both have good water solubility, low decomposition temperature, and few impurities after sintering, which can form a cerium-based oxide shell with high purity and uniform crystallization.

[0059] In step (2), the doped metal nitrate is any one of gadolinium nitrate hexahydrate, samarium nitrate hexahydrate, and yttrium nitrate hexahydrate. The radii of the three rare earth metal ions are well matched with those of cerium ions, and they can be stably doped into the cerium oxide lattice without causing lattice collapse. After doping, a large number of reversible oxygen vacancies can be continuously generated, which improves the medium-temperature conductivity of the material and effectively inhibits the high-temperature grain growth of cerium-based oxides, thereby improving the high-temperature operation stability and anti-aging ability of the cathode.

[0060] In step (2), the solvent is selected from a mixture of deionized water and one of ethanol, ethylene glycol and isopropanol in a volume ratio of 1:1. By mixing deionized water with organic solvent, the solubility of the precursor is ensured and the wettability of the solution in the cathode pores is improved.

[0061] In step (2), the concentration of solute in the precursor solution is 0.15-0.4 mol / L. This concentration range can avoid uneven or thin shell coating due to too low a concentration, or precursor aggregation or excessively thick shell blocking pores due to too high a concentration.

[0062] In step (2), the stirring is carried out at room temperature for 40-60 minutes; this ensures that the precursor is completely dissolved, forming a uniform and transparent solution, and ensuring the uniformity of subsequent impregnation load.

[0063] In step (3), the negative pressure is 0.05-0.09 MPa, and the heat preservation time is 25-30 min. This can remove the air trapped in the LSCF pores, open up the pore channels, and solve the problems of insufficient penetration and surface enrichment of conventional impregnation solutions; then the precursor solution is uniformly dripped onto the surface of the cathode blank.

[0064] In step (3), the atmospheric pressure immersion time is 15-40 min.

[0065] In step (3), the dropping speed is controlled at 0.5-1 mL / min. Low-speed uniform dropping can avoid the solution impacting and scouring the cathode coating, and ensure that the precursor solution wets the pores layer by layer. The drying conditions are: drying at 60-80℃ for 30-60 min. Low-temperature drying can slowly remove the solvent, prevent the rapid evaporation of the solvent from causing shell pores and cracks, and ensure the stability of the precursor adsorption layer structure.

[0066] In step (4), the impregnated blank is placed in a muffle furnace and heated to 300-450℃ at a heating rate of 2-4℃ / min and held for 1-3 hours to decompose and remove impurities such as nitrate and organic functional groups in the precursor, and to prevent porosity defects caused by high-temperature sintering; then heated to 800-1000℃ at a heating rate of 3-5℃ / min and held for 2-5 hours to allow the metal-doped cerium-based oxide to crystallize in situ on the surface of LSCF particles and form a uniform film, forming a dense core-shell interface; finally, it is cooled to room temperature with the furnace to avoid thermal mismatch and cracking of the shell and core layers caused by rapid cooling.

[0067] The solid oxide fuel cell cathode with a chromium-poisoning core-shell structure provided by this invention, through rare earth doping modification and core-shell structure design, combined with a two-phase conductivity mechanism, simultaneously improves the cathode's electronic conductivity, oxygen ion conduction, and oxygen reduction catalytic performance, effectively reducing battery polarization impedance and increasing battery output power density. Compared to pure LSCF cathodes, this product can maintain high catalytic activity under high-temperature conditions, solving the problem of severe high-temperature performance degradation of traditional cathodes. The ultra-thin porous rare earth metal-doped cerium-based shell can effectively isolate LSCF from direct contact with the external environment and electrolyte, inhibit high-temperature sintering agglomeration, element interdiffusion, and interface aging, and can block the contact between gaseous Cr and LSCF active sites. After long-term operation, no chromate is generated on the cathode surface, effectively solving the problem of cathode poisoning and degradation. At the same time, the gradient sintering process avoids structural cracking and detachment defects, significantly improving the stability of the cathode's mechanical and electrochemical structures, and greatly reducing the long-term cycle performance degradation rate.

[0068] The method for preparing a chromium-poison-resistant core-shell solid oxide fuel cell cathode provided by this invention employs conventional industrial processes such as screen printing, vacuum impregnation, and stepwise sintering. The parameters are precisely controllable, with good repeatability, and no complex, high-cost procedures. Through optimized design of the precursor system, impregnation parameters, and sintering regime, core-shell cathodes with uniform structure and consistent performance can be stably prepared, suitable for mass production and industrial application of large-size batteries. The chromium-poison-resistant core-shell solid oxide fuel cell cathode provided by this invention is compatible with various mainstream electrolyte systems such as YSZ, GDC, and LSGM. Based on the adaptability design of the GDC barrier layer, it is compatible with solid oxide fuel cells under different operating conditions, making it suitable for a wide range of applications. By precisely controlling the shell thickness, pore size, and doping ratio, a multi-dimensional balance is achieved in gas transport, reaction interface, ion conduction, and structural stability. This retains the high catalytic advantages of the LSCF core while overcoming its shortcomings in high-temperature stability and high interfacial impedance. The overall battery energy conversion efficiency and operational reliability are significantly better than traditional single cathode materials.

[0069] The present invention also provides a solid oxide fuel cell, which is prepared using the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure described in the present invention as the cathode. It has low polarization resistance and small attenuation after long-term operation at high temperature.

[0070] The present invention will now be described in detail with reference to the embodiments.

[0071] Unless otherwise specified, the raw materials used in each embodiment can be purchased from the market or prepared by referring to existing technologies.

[0072] In the various embodiments and comparative examples, the LSCF cathode slurry was prepared as follows: LSCF powder, terpineol, triethanolamine, and ethyl cellulose were dispersed by wet ball milling for 15-20 hours, followed by vacuum degassing to remove air bubbles, resulting in the cathode slurry. The mass ratio of each component was LSCF powder:terpineol:triethanolamine:ethyl cellulose = 60:30:0.8:7.5.

[0073] The terms used in the text are explained below:

[0074] LSCF: Lanthanum-Strontium-Cobalt Ferrite;

[0075] YSZ: Yttrium oxide stabilized zirconium oxide;

[0076] GDC: Gadolinium oxide doped with cerium oxide;

[0077] LSGM: Strontium and magnesium-doped lanthanum gallate.

[0078] Example 1

[0079] A solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure comprises a screen-printed LSCF as the core layer and a gadolinium-doped cerium-based oxide as the shell layer; the shell layer uniformly coats the surface of the core layer; the cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer; the electrolyte of the SOFC half-cell is made of YSZ material.

[0080] The method for preparing the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure includes the following steps:

[0081] (1) The LSCF cathode paste was uniformly printed on the surface of the GDC barrier layer of a SOFC half cell with a size of 10cm×10cm. The printing thickness was controlled at 20μm and the printing area size was 9cm×9cm. After printing, the LSCF cathode blank was pre-baked at 80℃ for 30min to obtain the LSCF cathode blank.

[0082] (2) Dissolve 9.77 g of cerium nitrate hexahydrate and 1.13 g of gadolinium nitrate hexahydrate (Ce:Gd molar ratio 9:1) in a mixed solvent of 50 mL of deionized water and 50 mL of ethanol, and stir magnetically at room temperature for 50 min to obtain a precursor solution with a solute concentration of 0.25 mol / L.

[0083] (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to a negative pressure of 0.08 MPa, and keep it warm for 30 min; then add the precursor solution to the surface of the cathode blank at a uniform dripping rate of 0.8 mL / min, impregnate at normal pressure for 30 min, and then dry at 70℃ for 60 min to obtain the impregnated blank;

[0084] (4) The impregnated blank is placed in a muffle furnace. First, the temperature is raised to 400℃ at a heating rate of 3℃ / min and held for 2h. Then, the temperature is raised to 900℃ at a heating rate of 4℃ / min and held for 3h. Finally, the blank is cooled to room temperature with the furnace to obtain the LSCF@GDC core-shell structure cathode with a shell thickness of 12nm.

[0085] Example 2

[0086] A solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure comprises a screen-printed LSCF as the core layer and a samarium-doped cerium-based oxide as the shell layer; the shell layer uniformly covers the surface of the core layer; the cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer; the electrolyte of the SOFC half-cell is made of YSZ material.

[0087] The method for preparing the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure includes the following steps:

[0088] (1) The LSCF cathode paste was uniformly printed on the surface of the GDC barrier layer of a SOFC half cell with a size of 10cm×10cm. The printing thickness was controlled at 25μm and the printing area size was 9cm×9cm. After printing, the LSCF cathode blank was pre-baked at 80℃ for 30min to obtain the LSCF cathode blank.

[0089] (2) Dissolve 9.77 g of cerium nitrate hexahydrate and 1.11 g of samarium nitrate hexahydrate (Ce: Sm molar ratio 9:1) in a mixed solvent of 50 mL of deionized water and 50 mL of ethanol, and stir magnetically at room temperature for 50 min to obtain a precursor solution with a solute concentration of 0.25 mol / L.

[0090] (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to a negative pressure of 0.08 MPa, and keep it warm for 30 min; then add the precursor solution to the surface of the cathode blank at a uniform dripping rate of 0.8 mL / min, impregnate at normal pressure for 30 min, and then dry at 70℃ for 60 min to obtain the impregnated blank;

[0091] (4) The impregnated blank is placed in a muffle furnace. First, the temperature is raised to 450°C at a heating rate of 3°C / min and held for 1 hour. Then, the temperature is raised to 850°C at a heating rate of 4°C / min and held for 2.5 hours. Finally, the blank is cooled to room temperature with the furnace to obtain the LSCF@SDC core-shell structure cathode.

[0092] Example 3

[0093] A solid oxide fuel cell cathode with a chromium-poisoning-resistant core-shell structure comprises a screen-printed LSCF as the core layer and a yttrium-doped cerium-based oxide as the shell layer; the shell layer uniformly coats the surface of the core layer; the cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer; the electrolyte of the SOFC half-cell is made of YSZ material.

[0094] The method for preparing the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure includes the following steps:

[0095] (1) The LSCF cathode paste was uniformly printed on the surface of the GDC barrier layer of a SOFC half cell with a size of 10cm×10cm. The printing thickness was controlled at 25μm and the printing area size was 9cm×9cm. After printing, the LSCF cathode blank was pre-baked at 80℃ for 20min to obtain the LSCF cathode blank.

[0096] (2) Dissolve 9.77 g of cerium nitrate hexahydrate and 0.96 g of yttrium nitrate hexahydrate (Ce:Y molar ratio 9:1) in a mixed solvent of 50 mL of deionized water and 50 mL of ethanol, and stir magnetically at room temperature for 50 min to obtain a precursor solution with a solute concentration of 0.25 mol / L.

[0097] (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to a negative pressure of 0.09 MPa, and keep it warm for 30 min; then add the precursor solution to the surface of the cathode blank at a uniform dripping rate of 1.0 mL / min, impregnate at normal pressure for 40 min, and then dry at 80℃ for 30 min to obtain the impregnated blank.

[0098] (4) The impregnated blank is placed in a muffle furnace. First, the temperature is raised to 300℃ at a heating rate of 2℃ / min and held for 3h. Then, the temperature is raised to 800℃ at a heating rate of 3℃ / min and held for 5h. Finally, the blank is cooled to room temperature with the furnace to obtain the LSCF@YDC core-shell structure cathode with a shell thickness of 15nm.

[0099] Comparative Example 1

[0100] A solid oxide fuel cell cathode uses a screen-printed LSCF as the core layer and LaO as the cathode material. .98 Ni 0.6 Fe 0.4 O3 forms the shell layer; the shell layer uniformly coats the surface of the core layer; the cathode is loaded on the surface of the SOFC half-cell with a GDC blocking layer; the electrolyte of the SOFC half-cell is made of YSZ material.

[0101] (1) The LSCF cathode paste was uniformly printed on the surface of the GDC barrier layer of a SOFC half cell with a size of 10cm×10cm. The printing thickness was controlled at 20μm and the printing area size was 9cm×9cm. After printing, the LSCF cathode blank was pre-baked at 80℃ for 30min to obtain the LSCF cathode blank.

[0102] (2) 4.29 g of lanthanum nitrate hexahydrate, 1.76 g of nickel nitrate hexahydrate, and 1.63 g of ferric nitrate nonahydrate (La:Ni:Fe molar ratio 9.8:6:4) were dissolved in a mixed solvent of 50 mL of deionized water and 50 mL of ethanol and stirred magnetically at room temperature for 50 min to obtain a LNF precursor solution with a solute concentration of 0.2 mol / L.

[0103] (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to a negative pressure of 0.08 MPa, and keep it warm for 30 min; then add the precursor solution to the surface of the cathode blank at a uniform dripping rate of 0.8 mL / min, impregnate at normal pressure for 30 min, and then dry at 70℃ for 60 min to obtain the impregnated blank;

[0104] (4) The impregnated blank is placed in a muffle furnace. First, the temperature is raised to 400℃ at a heating rate of 3℃ / min and held for 2h. Then, the temperature is raised to 900℃ at a heating rate of 4℃ / min and held for 3h. Finally, the blank is cooled to room temperature with the furnace to obtain an LSCF@LNF core-shell structure cathode with a shell thickness of 15nm.

[0105] Comparative Example 2

[0106] A solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure comprises a screen-printed LSCF as the core layer and a gadolinium-doped cerium-based oxide as the shell layer; the shell layer uniformly coats the surface of the core layer; the cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer; the electrolyte of the SOFC half-cell is made of YSZ material.

[0107] The method for preparing the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure includes the following steps:

[0108] (1) The LSCF cathode paste was uniformly printed on the surface of the GDC barrier layer of a SOFC half cell with a size of 10cm×10cm. The printing thickness was controlled at 20μm and the printing area size was 9cm×9cm. After printing, the LSCF cathode blank was pre-baked at 80℃ for 30min to obtain the LSCF cathode blank.

[0109] (2) Dissolve 9.77 g of cerium nitrate hexahydrate and 1.13 g of gadolinium nitrate hexahydrate (Ce:Gd molar ratio 9:1) in a mixed solvent of 50 mL of deionized water and 50 mL of ethanol, and stir magnetically at room temperature for 50 min to obtain a precursor solution with a solute concentration of 0.25 mol / L.

[0110] (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to a negative pressure of 0.08 MPa, and keep it warm for 30 min; then add the precursor solution to the surface of the cathode blank at a uniform dripping rate of 0.8 mL / min, impregnate at normal pressure for 30 min, and then dry at 70℃ for 60 min to obtain the impregnated blank;

[0111] (4) The impregnated blank is placed in a muffle furnace. First, the temperature is raised to 400℃ at a heating rate of 3℃ / min and held for 2h. Then, the temperature is raised to 780℃ at a heating rate of 4℃ / min and held for 3h. Finally, the blank is cooled to room temperature with the furnace to obtain the LSCF@GDC core-shell cathode with a shell thickness of 12nm.

[0112] Comparative Example 3

[0113] A method for preparing a solid oxide fuel cell cathode includes the following steps:

[0114] (1) The LSCF cathode paste was uniformly printed on the surface of the GDC barrier layer of a SOFC half cell with a size of 10cm×10cm. The printing thickness was controlled at 20μm and the printing area size was 9cm×9cm. After printing, the LSCF cathode blank was pre-baked at 80℃ for 30min to obtain the LSCF cathode blank.

[0115] (4) The LSCF cathode blank is placed in a muffle furnace. First, it is heated to 400℃ at a heating rate of 3℃ / min and held for 2h. Then, it is heated to 900℃ at a heating rate of 4℃ / min and held for 3h. Finally, it is cooled to room temperature with the furnace to obtain the LSCF cathode.

[0116] Test case

[0117] The solid oxide fuel cell cathodes prepared in the above embodiments and comparative examples were further prepared into SOFC full cells. The specific method is as follows: Anode and cathode current collector slurries were printed on the cell sheets of the solid oxide fuel cell cathodes prepared in the above embodiments and comparative examples, wherein the cathode current collector was lanthanum strontium cobalt oxide slurry LSCO and the anode current collector was nickel oxide slurry NiO; after printing, the cells were dried at 80°C to complete the preparation of SOFC full cells.

[0118] The performance of the SOFC full cells prepared in each embodiment and comparative example was tested, and the specific test methods are as follows:

[0119] ① Clamp the sealed battery, circulate air to raise the temperature and remove the adhesive, and replace with a hydrogen-nitrogen mixture to reduce the anode NiO at high temperature;

[0120] ② Maintain constant temperature and stability, calibrate fuel / air atmosphere, record open-circuit voltage and measure open-circuit EIS;

[0121] ③ The constant current step acquisition IV polarization curve is used, and the AC impedance EIS is measured after the current and voltage of each stage are stabilized;

[0122] ④ Change the temperature and conduct a comparison test;

[0123] ⑤ After the test is completed, switch off the protective nitrogen gas and allow the temperature to drop slowly;

[0124] ⑥ Fit the impedance using an equivalent circuit and separate the ohmic, activation, and concentration polarization impedances.

[0125] The battery cell measures 10cm x 10cm, the test temperature range is 650-700℃, the fuel H2 flow rate on the anode side is 500 sccm, and the air flow rate on the cathode side is 1500 sccm; the battery polarization impedance is obtained by adding the ohmic polarization impedance and the activation polarization impedance.

[0126] in Figure 2 The polarization impedance of the cell in its initial state at different temperatures, from Figure 2 It can be seen that the polarization impedance of each battery is similar at different temperatures. The initial polarization impedance of the full cell prepared by the LSCF cathode in Comparative Example 3 is relatively lower, while the impedance of the full cell prepared by the LSCF@GDC cathode at 780℃ in Comparative Example 2 is relatively higher. This is because pure LSCF has a better catalytic reduction effect on oxygen at the cathode than pure GDC, which can bring a lower battery activation impedance. However, the long-term anti-degradation performance of the LSCF@GDC cathode is significantly better.

[0127] The battery samples in the examples and comparative examples were tested under the following conditions: temperature 700°C and current density 0.3 A / cm². 2 With an H2 flow rate of 500 sccm and an air flow rate of 1500 sccm, the polarization impedance of the battery was tested after different periods of operation during power generation. Figure 3 As shown, the results indicate that the polarization impedance of the batteries in Examples 1 and 2 increases slowly with the length of operation time, reflecting less battery degradation; while the polarization impedance of the batteries in Comparative Examples 1-3 increases significantly with the length of operation time, reflecting greater battery degradation.

[0128] The battery samples in the examples and comparative examples were tested under the following conditions: temperature 700°C and current density 0.3 A / cm². 2With an H2 flow rate of 500 sccm and an air flow rate of 1500 sccm, the power generation operation was carried out for 5000 hours. After that, a portion of the cathode powder was taken for inductively coupled plasma atomic emission spectrometry (ICP) to test the Cr ion concentration. The results are shown in Table 1. The results show that the Cr content in the battery cathode powder prepared in Examples 1-3 is lower, while the Cr content in the battery cathode powder prepared in Comparative Examples 1-3 is higher. It can be seen that the solid oxide fuel cell cathode provided in the examples can better resist chromium poisoning.

[0129] Table 1

[0130]

[0131] As can be seen from the above, the solid oxide fuel cell cathode with anti-chromium poisoning core-shell structure provided by the present invention can effectively reduce the polarization impedance of the battery during long-term operation at high temperature. Its metal-doped cerium-based oxide shell has a physical barrier effect, which can block the contact between gaseous Cr and the active sites of LSCF. After long-term operation, no chromate is generated on the cathode surface, effectively solving the problem of cathode poisoning and degradation.

[0132] The above detailed description of a solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure and its preparation method, with reference to the embodiments, is illustrative rather than limiting. Several embodiments may be listed within the defined scope. Therefore, variations and modifications without departing from the overall concept of the present invention should be within the protection scope of the present invention.

Claims

1. A solid oxide fuel cell cathode with a core-shell structure resistant to chromium poisoning, characterized in that, The solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure uses a screen-printed LSCF as the core layer and a metal-doped cerium-based oxide as the shell layer; the shell layer is uniformly coated on the surface of the core layer; the solid oxide fuel cell cathode is loaded on the surface of an SOFC half-cell with a GDC barrier layer.

2. The solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure according to claim 1, characterized in that, In the metal-doped cerium-based oxide, the molar ratio of cerium to the doped metal element is (8-9.5):(0.5-2).

3. The solid oxide fuel cell cathode with a chromium-poison-resistant core-shell structure according to claim 1 or 2, characterized in that, The shell has a thickness of 10-25 nm and a porous structure with a pore size of 5-12 nm.

4. The solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure according to claim 1 or 2, characterized in that, The LSCF core layer is printed with a thickness of 15-25 μm.

5. The solid oxide fuel cell cathode with a chromium-poison-resistant core-shell structure according to claim 1 or 2, characterized in that, In the metal-doped cerium-based oxide, the doping metal element is any one of gadolinium, samarium, and yttrium.

6. The solid oxide fuel cell cathode with a chromium poisoning-resistant core-shell structure according to claim 1 or 2, characterized in that, The electrolyte material of the SOFC half-cell is any one of YSZ, GDC, or LSGM.

7. The method for preparing a solid oxide fuel cell cathode with a chromium-poison-resistant core-shell structure as described in any one of claims 1-6, characterized in that, The preparation method includes the following steps: (1) The LSCF cathode paste is uniformly printed on the surface of the GDC barrier layer of the SOFC half cell. After printing, it is pre-baked to obtain the LSCF cathode blank. (2) Dissolve the cerium source and the doped metal nitrate in a solvent, stir until homogeneous, and obtain a precursor solution; (3) Place the LSCF cathode blank in a vacuum impregnation vessel, close the vessel and evacuate to negative pressure for heat preservation; then add the precursor solution to the surface of the cathode blank at a uniform rate, impregnate at normal pressure, and then dry to obtain the impregnated blank; (4) Heat the impregnated blank to 300-450℃ and hold for 1-3 hours, then heat to 800-1000℃ and hold for 2-5 hours, and finally cool to room temperature with the furnace to obtain LSCF@metal-doped cerium-based oxide core-shell structure cathode.

8. The preparation method according to claim 7, characterized in that, In step (1), the thickness of the printing is 15-25 μm.

9. The preparation method according to claim 7, characterized in that, In step (1), the pre-drying conditions are: 75-85℃ for 20-30 minutes.

10. The preparation method according to claim 7, characterized in that, In step (2), the cerium source is one of cerium nitrate hexahydrate or cerium acetate tetrahydrate.

11. The preparation method according to claim 7, characterized in that, In step (2), the doped metal nitrate is any one of gadolinium nitrate hexahydrate, samarium nitrate hexahydrate, and yttrium nitrate hexahydrate.

12. The preparation method according to claim 7, characterized in that, In step (2), the solvent is selected from a mixture of deionized water and one of ethanol, ethylene glycol and isopropanol in a volume ratio of 1:

1.

13. The preparation method according to claim 7, characterized in that, In step (2), the concentration of solute in the precursor solution is 0.15-0.4 mol / L.

14. The preparation method according to claim 7, characterized in that, In step (3), the negative pressure is 0.05-0.09 MPa and the heat preservation time is 25-30 min.

15. The preparation method according to claim 7, characterized in that, In step (3), the atmospheric pressure immersion time is 15-40 min.

16. The preparation method according to claim 7, characterized in that, In step (3), the dropping speed is controlled at 0.5-1 mL / min; the drying conditions are: drying at 60-80℃ for 30-60 min.

17. The preparation method according to claim 7, characterized in that, In step (4), the impregnated blank is placed in a muffle furnace. First, the temperature is raised to 300-450℃ at a heating rate of 2-4℃ / min and held for 1-3 hours. Then, the temperature is raised to 800-1000℃ at a heating rate of 3-5℃ / min and held for 2-5 hours. Finally, the blank is cooled to room temperature with the furnace.

18. A solid oxide fuel cell, characterized in that, The solid oxide fuel cell is prepared using the solid oxide fuel cell cathode with the chromium poisoning-resistant core-shell structure as described in any one of claims 1-6 as the cathode.